Download presentation

Presentation is loading. Please wait.

Published byKenya Warren Modified over 2 years ago

2
Function Composition

3
Fancy way of denoting and performing SUBSTITUTION But first …. Let’s review.

4
Function Composition Function notation: f(x) This DOES NOT MEAN MULITPLICATION. Given f(x) = 3x - 1, find f(2). Substitute 2 for x f(2) = 3(2) - 1 = 6 - 1 = 5

5
Function Composition Given g(x) = x 2 - x, find g(-3) g(-3) = (-3) 2 - (-3) = 9 - -3 = 9 + 3 = 12 g(-3) = 12

6
Function Composition Given g(x) = 3x - 4x 2 + 2, find g(5) g(5) = 3(5) - 4(5) 2 + 2 = 15 - 4(25) + 2 = 15 - 100 + 2 = -83 g(5) = -83

7
Function Composition Given f(x) = x - 5, find f(a+1) f(a + 1) = (a + 1) - 5 = a+1 - 5 ]f(a + 1) = a - 4

8
Function Composition Function Composition is just fancy substitution, very similar to what we have been doing with finding the value of a function. The difference is we will be plugging in another function

9
Function Composition Just the same we will still be replacing x with whatever we have in the parentheses. The notation looks like g(f(x)) or f(g(x)). We read it ‘g of f of x’ or ‘f of g of x’

10
Function Composition Some books use [f °g](x) for f(g(x)) and [g ° f](x) for g(f(x)). Other books use f °g(x) and g ° f(x)

11
Function Composition EXAMPLE Given f(x) = 2x + 2 and g(x) = 2, find f(g(x)). Start on the inside. f(g(x)) g(x) = 2, so replace it. f(g(x)) = f(2) = 2(2) + 2 = 6

12
Function Composition Given g(x) = x - 5 and f(x) = x + 1, find f(g(x)). g(x) = x - 5 so replace it. f(g(x)) = f(x - 5) Now replace x with x - 5 in f(x).

13
Function Composition f(x - 5) = (x - 5) + 1 = x - 5 + 1 = x - 4 So f(g(x)) = x - 4. Find g(f(x)). Well f(x) = x + 1 so replace it. g(x + 1). g(x + 1) = x + 1 - 5 = x - 4

14
Function Composition Given f(x) = x 2 + x and g(x) = x - 4, find f(g(x)) and g(f(x)). f(g(x)) = f(x - 4) = (x - 4) 2 + (x - 4) = x 2 - 8x+16+x - 4 = x 2 - 7x+12 f(g(x)) = x 2 - 7x + 12

15
Function Composition Given f(x) = x 2 + x and g(x) = x - 4, find f(g(x)) and g(f(x)). g(f(x)) = g(x 2 + x) = x 2 + x - 4

16
Function Composition Given f(x) = 2x + 5 and g(x) = 8 + x, find f(g(-5)). Start in the middle: g(-5) = 8 + -5 = 3. So replace g(-5) with 3 and we get f(3) = 2(3) + 5 = 6 + 5 = 11

17
Function Composition Given f(x) = 2x + 5 and g(x) = 8 + x, find g(f(-5)). Start in the middle: f(-5) = 2(-5) + 5 = -10 + 5 = 5 Replace f(-5) with 5 and we have g(5) = 8 + 5 = 13. g(f(-5)) = 13

18
Function Composition Assignment:

Similar presentations

© 2017 SlidePlayer.com Inc.

All rights reserved.

Ads by Google